Green infrastructure transitional management sphere analysis of policies and regulations in Kuala Lumpur, Malaysia - Thian, Owen Seng Yeo; Mohd Yusof, Mohd Johari; Maruthaveeran, Sreetheran; Saito, Kei; Abu Kasim, Junainah (Malaysia Institute of Planners, 2022)
Kuala Lumpur (KL) is experiencing rapid development leading to urban green space fragmentation. Green infrastructure (GI) could be the answer to the fragmented green space issue. Nevertheless, how policies and legislations contribute to the spatial establishment of GI in KL remains unclear. Thus, the policies and regulations governing GI establishment in KL were examined in this study. A total of 77 records associated with policies and regulations that may contribute to GI spatially were reviewed. In order to evaluate the efficacy of the chosen articles, the transition management sphere analysis was applied. The study discovered that Malaysia is still lacking in GI policies and regulations. Furthermore, this study also highlighted different challenges and opportunities during optimising GI implementation in spatial design. The finding can be a reference for future policy and regulation establishment.